PENGEMBANGAN BUKU AJAR BAHASA INDONESIA TERINTEGRASI PENDIDIKAN KARAKTER BERDASARKAN PENDEKATAN KOMUNIKATIF - Erika, Cicilia Nian (Jurnal Pendidikan Bahasa dan Sastra, 2019)
The research and development of Indonesian textbooks is very important especially for the textbook which integrates character education using communicative approach. Many textbooks have been published, but they are often only for reference in assignments and exercises. The existing textbooks do not fully use text that is a genre in learning Indonesian, namely the pedagogic genre. This research aims to produce forms of competence, material forms, forms of tasks, and forms of assessment in the development of Indonesian Language and Literature textbooks integrated with character education based on communicative approaches for junior high school. The method used was research and development with reference to the Borg and Gall model. The showed that learning devices, teaching books, are feasible to implement. In addition, practitioners' assessment of the implementation of this textbook is 3,526 categories "Good". Likewise, the assessment of students in the three aspects occupies the highest category of Good. Therefore, the development of the Indonesian Language and Literature textbook can already be said to be feasible to use for the teachers and the students of Junior High School, especially for SMP Pangudi Luhur 1 Â in Yogyakarta.